Research and Technology for the Social Inclusion of People with Hearing Impairment - Hernández, Cesar; Sánchez, Juan; Giral, Diego (Journal of Ecohumanism, 2024)
People with hearing impairments face challenges that affect their communication and social inclusion. Sign language is a key communication system that improves the level of social inclusion of the hearing-impaired population. To address this, our collaborative work aims to develop a technological tool that enhances the initial learning of sign language in children with hearing impairments. This tool, developed with the use of information and communication technologies and the advice of professionals in special education, is designed to specifically facilitate the learning of sign language in deaf children. Our tests have demonstrated its effectiveness, with a 30% reduction in the initial learning time of sign language in deaf children.